Pengaruh Pemberian Sub Soil dan Arang Tempurung Kelapa Terhadap Pertumbuhan Semai Akasia (Acacia mangium. Willd) Pada Media Bekas Tambang Pasir - Basuki Wasis; Lastiti Sanubari (Jurnal Silvikultur Tropika, 2019)
Sand mining which continuously done may cause the sand of amount in the bottom of river decreasing and may result, to the destruction of the river if occured for a long period. Revegetation activity must be done on some former sand mining river boundaries. Acacia (Acacia mangium) might be able to grow in low nutrient soil. The purposes of this research is to get information about sub soil and coconut charcoal granting effects towards acacia seedling growth on former sand mining medium.The research showed that the interaction of the added sub soil and coconut shell charcoal is significant to the heightand diameter parameter of acacia seedling while sub soil addition is significant to Dry Weight Total (DWK) parameter. Interaction of 250 g sub soil, 60 g charcoal on 750 g sand is the best treatment to enhance seedling tall growth for about 88.73%. Interaction of 750 g sub soil on 250 g sand is the most significant treatment for diameter parameter for about 71.21% diameter growth. The best treatment for Dry Weight Total (DWK) is shown by interaction of 250 g sub soil and 250 g charcoal on 500 g sand. Charcoal granting independently is not significant to addition acacia seedling growth. The addition of sub soil only showed the best result of 750 g sub soil granting with diameter growth around 71.21%. Key words: Acacia mangium. Willd., charcoal, sand mining, sub soil